1403 Leadership and Teamwork in The Major Trauma Service – Implementation of A New Approach to Secondary Surveys. (12th October 2021) - Jefferies, O; Walls, A; McKeag, P; Houston, R; Kealey, D
Abstract: Aim: Trauma Audit and Research Network (TARN) guidelines at a Major Trauma Centre in Northern Ireland state that all patients admitted with Major Trauma should have a secondary survey completed and documented within 24 hours of admission. Method: All patients admitted with major trauma had their medical notes reviewed on discharge to look for evidence of a documented secondary survey. Two audit cycles were completed. The first from January 2018 to April 2018 (n = 38). Following a quality improvement project with specific interventions to improve compliance, including improved communication behaviours and the implementation of a revised trauma booklet, a second cycle was performed from October 2019 to January 2019 (n = 44) Results: 58% of group 1 and 75% of group 2 had a documented secondary survey within 24 hours of admission. The interventions therefore resulted in an overall 17% increase in the number of secondary surveys completed within 24 hours. Patients admitted under Orthopaedic care had a significant improvement of 26% between cycles to 89% compliance. Cardiothoracics (33% to 40%), Neurosurgery (14% to 43%) and General Surgery (75% to 66%). Conclusions: A quality improvement drive led by the Orthopaedic team involving the education of doctors, improving communication channels and the introduction of revised trauma documentation, resulted in a significant increase in the number of secondary surveys completed within 24 hours. Patients under the care of Orthopaedics were more likely to have a survey completed compared with other specialties. This highlights the need for more education and engagement of other specialities to increase compliance in secondary surveys.